POTENSI TERAPI DARI NUTRASETIKAL DALAM UPAYA PENCEGAHAN PENYAKIT INFEKSI VIRUS - Dea Okta Pabiola; Khairun Nisa Berawi; Giska Tri Putri (Jurnal Ilmu Kedokteran dan Kesehatan, 2022)
Abstract: Therapeutic Potential of Nutraceuticals in The Prevention of Viral Disease. Viral infectious diseases are a major cause of morbidity worldwide with the potential to increase their spread, turning them into pandemics. Nutrition can play a major role in supporting the immune system and its optimal function. A healthy diet contained in nutraceuticals can play an important role in boosting the immune system and fighting various viral invasions. The aim of this journal is to provide comprehensive information on dietary-based scientific recommendations, evidence, and case studies around the world regarding viral infections, particularly in the current pandemic. The method used is a literature review. After reviewing the immune potential of nutraceuticals based on laboratory studies and human studies, it was concluded that bioactive compounds such as resveratrol, quercetin, curcumin, epigallocatechin gallate (EGCG), N-acetyl cysteine (NAC), and palmitoylethanolamide (PEA) with proven antiviral properties enhance the immune system. immune system thus plays an important role in treating various infections caused by viruses in addition to strengthening the immune system.Keywords: nutraceutical, immune system, viral infection